Biosynthesis and processing of a Plasmodium falciparum schizont antigen recognized by immune serum and a monoclonal antibody (The Rockefeller University Press, 1982)
Stage-specific protein synthesis by the erythrocytic forms of the malaria parasite Plasmodium falciparum was investigated by pulse labeling synchronous parasite cultures with [35S]methionine at 6-h intervals during a complete 48-h developmental cycle. About 40 labeled parasite proteins could be immunoprecipitated with human immune serum, and most of these were associated with the schizont stage of development. In particular, one schizont protein was a 195,000-mol wt species against which a murine monoclonal antibody was produced. This monoclonal antibody, 89.1 reacted with the parasite membrane in schizonts and also with the surface of free merozoites in the indirect immunofluorescence test. In addition to the 195,000-mol wt protein, antibody 89.1 immunoprecipitated a series of lower-molecular weight polypeptides from extracts of labeled asynchronous P. falciparum parasite cultures. These were shown to be related to the 195,000-mol wt protein by peptide mapping. Pulse-chase labeling of synchronized cultures, and immunoprecipitation with antibody 89.1, showed that specific processing of the 195,000-mol wt polypeptide to the lower- molecular-weight products in concomitant with schizont maturation and merozoite release. It is suggested that this P. falciparum protein may be analogous to a similarly processed 230,000-mol wt protective antigen of the rodent malaria parasite, P. yoelii.